RANCANG BANGUN MESIN ABSENSI TANPA MENYENTUH DENGAN RFID - Rizki Faulianur; Inzar Salfikar (Politeknik Aceh, 2022)
In education, attendance is very important for lecturers and students. Currently, attendance used in universities still uses signatures or fingerprints so that there is direct contact with certain objects. But in the current pandemic. students and lecturers are required to keep their distance and avoid physical contact with shared objects because they can spread the virus quickly. This Attendance machine is offered to limit direct contact and inhibit the spread of the coronavirus by using Radio Frequency Identification (RFID) as a method of controlling Raspberry pi. RFID will generate a unique code that is used as user data which will then be stored with Raspberry pi and then stored in the database. RFID can read the reader within a range of 3 cm. From the test results, this machine is able to recognize 3 users who detect and process data quickly